Efforts to Improve Students’ Learning Outcomes Through Collaborative Learning: The Topic of Quadrilaterals - Nasution, Nurul Rafiqah; Wahyudin, Wahyudin; Nurlaelah, Elah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Collaborative learning has been proven beneficial in mathematics education. This study aims to enhance learning outcomes through collaborative learning, particularly focusing on the topic of quadrilaterals. The research method employed in this study is classroom action research. Data analysis for this research utilizes both quantitative and qualitative data. The research findings indicate that: (1) students' learning outcomes prior to implementing collaborative learning were incomplete as students did not achieve the targeted indicators; (2) students' learning outcomes improved after the implementation of collaborative learning in both Cycle I and Cycle II; (3) the overall class achievement in Cycle I showed an improvement compared to the pre-action phase. Meanwhile, the mastery of learning between Cycle I and Cycle II showed further improvement, becoming even better; (4) observation results of the teacher's activities in facilitating collaborative learning in Cycle I were rated as moderately good, while in Cycle II, they were rated as very good; (5) students' responses during the collaborative learning process in Cycle I were categorized as moderately good, whereas in Cycle II, they were categorized as very good.